Main parameters for information security intruder identification - Гізун, Андрій Іванович; Волянська, Владислава Вікторівна; Риндюк, Вікторія Олександрівна; Гнатюк, Сергій Олександрович (Ukrainian Information Security Research Journal, 2013)
Studying of the person of information security intruder has a great scientific and practical importance. In addition accordingly to normative documents intruders and threats models development is important stage in development of effective information security systems. From this viewpoint parameters formalization for intruder identification is an actual research problem. The solving of this problem is a subject of the paper. Definition of complete set (cortege) of host and network parameters can give a possibility to consider features of attacks (from people or robots) and to increase preventive measures & security systems efficiency. Given results can be the basis for intrusion detection systems based on honeypot-technology development.